Physicians' Attire Influences Patients' Perceptions in the Urban Outpatient Orthopaedic Surgery Setting. Issue 9 (September 2016) - Jennings, John D.; Ciaravino, Sophia G.; Ramsey, Frederick V.; Haydel, Christopher
Abstract: Background: Previous work has established that physician attire influences patients' perceptions of their physicians. However, research from different specialties has disagreed regarding what kinds of physician attire might result in increased trust and confidence on the part of patients. Questions/Purposes: The purpose of this study was to investigate how surgeon attire affects patients' perceptions of trust and confidence in an urban orthopaedic outpatient setting. Methods: Eighty‐five of 100 patients solicited completed a three‐part questionnaire in the outpatient orthopaedic clinic at an urban teaching hospital. In the first section, participants viewed eight images, four of a male surgeon and four of a female surgeon wearing a white coat over formal attire, scrubs, business attire, and casual attire, and rated each image on a five‐level Likert scale. Participants were asked how confident, trustworthy, safe, caring, and smart the surgeon appeared, how well the surgery would go, and how willing they would be to discuss personal information with the pictured surgeon. The participant ranked all images from most to least confident in the second part and the last section obtained demographic information from the patients. Surveys were scored using a five‐level Likert scale and a Friedman test was used to detect statistical significance when comparing all attires. For multiple pairwise comparisons, a Bonferroni correction was applied. Results: The white coat on the male surgeon elicited modestly higher ratings in confidence (mean difference [MD], 0.367 ± 0.737; 95% CI, 0.202‐0.532; p < 0.001), intelligence (MD, 0.216 ± 0.603; 95% CI, 0.077‐0.356; p = 0.027), surgical skill (MD, 0.325 ± 0.658; 95% CI, 0.175‐0.474; p < 0.001), trust (MD, 0.312 ± 0.613; 95% CI, 0.173‐0.451; p < 0.001), ability to discuss confidential information (MD, 0.253 ± 0.742; 95% CI, 0.087‐0.419; p = 0.023), caring (MD, 0.279 ± 0.655; 95% CI, 0.124‐0.432; p = 0.006), and safety (MD, 0.260 ± 0.594; 95% CI, 0.125‐0.395; p = 0.002) compared with business attire. Similarly, the white coat was preferred to casual attire in all categories (confidence: MD, 0.810 ± 0.921; smart: MD, 0.493 ± 0.801; surgical skill: MD, 0.640 ± 0.880; ability to discuss: MD, 0.564 ± 0.988; trust: MD, 0.545 ± 0.836; safety: MD, 0.581 ± 0.860; caring: MD, 0.479 ± 0.852; p < 0.001 for all comparisons). For the female surgeon, white coat and scrubs were not different, however the white coat was preferred to business attire in four of seven categories. Casual clothing was widely disliked in all categories for surgeons (men and women). When attire was compared for confidence on a scale, the white coat ranked higher than business (MD, 0.439 ± 1.491; p = 0.006) and casual attire (MD, 1.043 ± 2.054; p < 0.001), but not scrubs (MD, 0.169 ± 1.230; p = 1.000). Conclusions: In this urban outpatient orthopaedic practice, patients' preferences varied based on the sex of the pictured surgeon in the survey. Overall, however, modest preferences were observed for the white coat in terms of confidence, intelligence, trust, and safety. Furthermore patients are more willing to discuss personal information and believe that their surgery will go better if the surgeon wears a white coat or scrubs. These results are consistent with those of several studies in other settings and therefore may be generalizable in other locations and specialties. Given the increasing awareness and concern for physician‐spread hospital infection, this study lends support to scrub attire over business or casual attire if physicians do not wear a white coat. Level of Evidence: Level II, therapeutic study.